The Author’s Pale and Glaring Head on a Platter: The Intricacies of the Concept of Untranslatability - Barciński, Łukasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The article deals with the issue of untranslatability, a concept frequently re-emerging in the translation discourse. It seems that in many cases the possible search for the equivalence between the source language and the target language does not consist in a binary choice between the possibility and impossibility of performing a translation, but can be better described as a cline of translatability or the latent potential for linguistic transposition. In view of the inherent anisomorphism between linguistic codes i.e. the fact that there are no exact correspondences between words in different languages, it is important to cast off the misleading illusion of linguistic symmetry for the purpose of translation theory and practice. In other words, it seems essential to perceive the translation process in terms of the reincarnation metaphor rather than the transfer metaphor which presupposes the notion of absolute translatability. The article includes also an attempt at a categorisation of types of translation from the epistemological or phenomenological point of view.
Keywords: untranslatability; translation discourse; anisomorphism; metaphor